Activation and Contraction of Human “Vascular” Smooth Muscle Cells Grown From Circulating Blood Progenitors - Ahmetaj-Shala, Blerina; Marei, Isra; Kawai, Ryota; Rothery, Stephen; Pericleous, Charis; Mohamed, Nura A.; Gashaw, Hime; Bokea, Kalliopi; Samuel, Jake; Vandenheste, Annabelle; Shala, Fisnik; Kirkby, Nicholas S.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Blood outgrowth smooth muscle cells offer the means to study vascular cells without the requirement for surgery providing opportunities for drug discovery, tissue engineering and personalised medicine. However, little is known about these cells which has meant their therapeutic potential remains unexplored. Our objective was to investigate for the first time the ability of blood outgrowth smooth muscle cells and vessel derived smooth muscle cells to sense the thromboxane mimetic U46619 by measuring intracellular calcium elevation and contraction. U46619 increased cytosolic calcium in blood outgrowth smooth muscle cells and vascular smooth muscle cells. Increased calcium signal peaked between 10-20 seconds after U46619 in both smooth muscle cell types. Importantly, U46619 induced concentration-dependent contractions of both blood outgrowth smooth muscle cells and vascular smooth muscle cells. In summary, we show that responses of blood outgrowth smooth muscle cells parallel vascular smooth muscle cells providing critical evidence of their application in biomedical research.